The Absorptive Capacity and Knowledge Sharing Models on Seblak MSMEs Business Performance in Bekasi - Syahyono; Chusnul Rahmawati; Devi Virgiana Hermansyah; Erika Nurhayani; Arianto, Quanita Elisya (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study analyzes the influence of absorptive capacity and knowledge sharing on the business performance of Seblak MSMEs in Bekasi City. In the increasingly competitive food industry, absorptive capacity, as an organization's ability to acquire, assimilate, and utilize external knowledge, becomes an important factor for innovation and market response. In addition, knowledge sharing also supports the exchange of information and expertise within and between organizations, thereby improving product quality and operational efficiency. Through a descriptive quantitative approach, data were collected from 100 MSMEs through purposive sampling techniques and analyzed using the SEM-PLS (Structural Equation Modeling Partial Least Squares) method. The results reveal that absorptive capacity and knowledge sharing have a significant and positive influence on business performance, both directly and through synergistic interactions. The findings emphasize the importance of structured knowledge management and a culture of collaboration to drive innovation and improve competitiveness. The practical implications of this study include recommendations for MSMEs to strengthen absorptive capacity and optimize knowledge sharing practices as a strategy to improve market position and business sustainability.